Pengaruh Intellectual Capital Terhadap Kinerja Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Suprayogi, M. Dodik; Karjati, Pratiwi Dwi (Economie: Jurnal Ilmu Ekonomi, 2020)
The Intellectual Capital concept emerged because of the industrial-based economic shift towards knowledge-based. From previous research it was known that IC had an effect on the company's financial performance. With the competitive advantage that the company has, it will improve the performance of the company itself. So that IC can be said as an intangible asset that has a significant impact on performance and all success in business. Therefore the author wants to examine more about "The Effect of Intellectual Capital on the Performance of Banking Companies Listed on the Indonesia Stock Exchange". By using a quantitative research approach, where the population in this study are all banking companies (commercial banks) operating in Indonesia from 2014 to 2017 which routinely (tri wulan) report their financial position to Bank Indonesia (BI), which is 115 banks, then taken a sample of 44 companies using purposive sampling technique. The independent variable in this study is Value Added Intellectual Coefficient (VAIC ™) consisting of Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA). The dependent variable is the company's financial performance which consists of Risk profile, Good Corporate Governance, Earning, and Capital (RGEC). Testing the hypothesis in this study using PLS (β and γ) is done by bootstrap resampling method. And from the results of the analysis it is known that Intellectual capital does not have a significant effect on Non Performing Loans (NPL) but found that the Intellectual capital has a significant effect on the Loan to Deposit Ratio (LDR), Good Corporate Governance (GCG), Return On Asset ( ROA), Net Interest Margin (NIM) and Capital Adquency Ratio (CAR)